Cu‐Mediated Direct Aryl CH Halogenation: a Strategy to Control Mono‐ and Di‐Selectivity. Issue 1 (31st October 2013) - Du, Zhi‐Jun; Gao, Lian‐Xun; Lin, Ying‐Jie; Han, Fu‐She
Abstract A protocol for the copper‐mediated direct aryl CH halogenation is presented. Highly selective mono‐ and di‐halogenations are achieved by using acyl hypohalites, generated in situ from the readily available carboxylic acid and N‐halosuccinimides (NXS; X=Br and Cl) as powerful halogenating reagents. The correct choice of carboxylic acid additives and solvents is essential for both high yield and selectivity. Consequently, the use of inexpensive Cu catalyst and the new strategy for the in situ generation of acyl hypohalite halogenating reagents from the readily affordable and easily‐to‐handle carboxylic acid and NXS (X=Br and Cl) offers advantages for practical application.